Virtue and Vice: Consumer Culture in English Canadian Fiction Before 1940 - Belisle, Donica (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
This article explores references to commodities and consumption in English language fiction either written by Canadians or published in Canada between 1890 and 1940. It confirms and expands existing research into Canadian consumer history by showing that consumer themes were central to authors’ portrayals of class, gender, and morality. Suggesting that fiction offers important historical perspectives on English Canadian culture, it demonstrates that as Canada became an industrial, urban, and capitalist nation, consumer desire and display became central to English Canadian fiction writers’ portrayals of identity, status, and opportunity.